Evaluasi dan Perancangan User Interface untuk Meningkatkan User Experience Menggunakan Metode Human-Centered Design dan Heuristic Evaluation Pada Aplikasi Ezypos - Anita Putri Novitasari; Herman Tolle; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
EzyPOS is an application to simplify the work of owners of Micro, Small and Medium Enterprises in managing their businesses to be better and organized. The use of the EzyPOS application is the same as the cash register. There are several usability problems in the EzyPOS Application such as button size which doesn't suits the standart so that have an effect on user experience. Recommendations for User interface and User Experience improvement along with the results of evaluation and analysis of both are the objectives of this study An approach that is used is human-centered design (HCD) which is a system design and development approach to make interactive systems more useful by focusing on the use of systems and applying human factors / ergonomics and usability knowledge and techniques. The HCD stages are context specifications, User specifications, design, and design evaluation. Evaluation Method which is used is a Heuristic Evaluation (HE) which is a method for finding usability problems in the User interface by using 3-5 evaluators to examine and assess it in accordance with the applicable usability principles. Improvements are made based on saverity rating. The results of this study are the solution design with the HCD approach which has better usability than the EzyPOS application version 1.0.19. This is indicated by the decrease in number of problems found in the EzyPOS solution design, namely from 20 to 6 problems.